Staphylococcal SSL5 Binding to Human Leukemia Cells Inhibits Cell Adhesion to Endothelial Cells and Platelets - Annemiek M. E. Walenkamp; Jovanka Bestebroer; Ingrid G. J. Boer; Roeline Kruizinga; Henk M. Verheul; Jos A. G. van Strijp; Carla J. C. de Haas (Cellular Oncology)
Bacterial proteins provide promising tools for novel anticancer therapies. Staphylococcal superantigen-like 5 (SSL5) was recently described to bind P-selectin glycoprotein ligand-1 (PSGL-1) on leukocytes and to inhibit neutrophil rolling on a P-selectin surface. As leukocytes and tumor cells share many characteristics in migration and dissemination, we explored the potential of SSL5 as an antagonist of malignant cell behavior. Previously, it was demonstrated that rolling of human HL-60 leukemia cells on activated endothelial cells was mediated by P-selectin. In this study, we show that SSL5 targets HL-60 cells. Binding of SSL5 was rapid and without observed toxicity. Competition of SSL5 with the binding of three anti-PSGL-1 antibodies and P-selectin to HL-60 cells identified PSGL-1 as the ligand on HL-60 cells. Presence of sialyl Lewis x epitopes on PSGL-1 was crucial for its interaction with SSL5. Importantly, SSL5 not only inhibited the interaction of HL-60 cells with activated endothelial cells but also with platelets, which both play an important role in growth and metastasis of cancers. These data support the concept that SSL5 could be a lead in the search for novel strategies against hematological malignancies.